2021
DOI: 10.7150/thno.58468
|View full text |Cite
|
Sign up to set email alerts
|

Major vault protein (MVP) negatively regulates osteoclastogenesis via calcineurin-NFATc1 pathway inhibition

Abstract: Rationale: Bone homeostasis is maintained by a balanced interplay of osteoblasts and osteoclasts. Osteoclasts are derived from monocyte/macrophage lineage. Major vault protein (MVP) is known to promote apoptosis and prevent metabolic diseases in macrophage. However, whether MVP is involved in osteoclastogenesis is unknown. Here, we identified an important function of MVP as a negative regulator of osteoclastogenesis and its therapeutic potential in preventing bone loss. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…The induction of MVP expression by viral infection upregulates type-I interferon production by enhancing the expression of IRF7 (interferon regulatory factor 7), but not IRF3 (interferon regulatory factor 3) [ 105 ]. Moreover, MVP inhibits the calcineurin-NFATc1 signaling pathway, which regulates genes involved in intracellular calcium concentrations, negatively regulating osteoclast differentiation and bone resorption [ 140 ]. MVP is also closely connected to signaling pathways in cancer cells, and upregulation most often results in chemotherapy resistance of the cells.…”
Section: Mvp and The Vault Complex: Implications To Cell Proliferatio...mentioning
confidence: 99%
“…The induction of MVP expression by viral infection upregulates type-I interferon production by enhancing the expression of IRF7 (interferon regulatory factor 7), but not IRF3 (interferon regulatory factor 3) [ 105 ]. Moreover, MVP inhibits the calcineurin-NFATc1 signaling pathway, which regulates genes involved in intracellular calcium concentrations, negatively regulating osteoclast differentiation and bone resorption [ 140 ]. MVP is also closely connected to signaling pathways in cancer cells, and upregulation most often results in chemotherapy resistance of the cells.…”
Section: Mvp and The Vault Complex: Implications To Cell Proliferatio...mentioning
confidence: 99%
“…Vaults are highly conserved across species and most mammalian cell vaults are in the cytoplasm ( Esfandiary et al, 2009 ). Research suggested that MVP negatively regulates osteoclast differentiation and bone resorption via inhibition of calcineurin-NFATc1 signaling and Mvp−/− and Mvp f/f Lyz2-Cre mice both exhibited osteoporosis-like phenotypes ( Yuan L. et al, 2021 ). MVP-deficiency also enhanced calcineurin-NFATc1 signaling and promoted NFATc1 activity, which led to enhanced osteoclastogenesis and bone resorption ( Yuan L. et al, 2021 ).…”
Section: The Differentiation Of Osteoclastsmentioning
confidence: 99%
“…Research suggested that MVP negatively regulates osteoclast differentiation and bone resorption via inhibition of calcineurin-NFATc1 signaling and Mvp−/− and Mvp f/f Lyz2-Cre mice both exhibited osteoporosis-like phenotypes ( Yuan L. et al, 2021 ). MVP-deficiency also enhanced calcineurin-NFATc1 signaling and promoted NFATc1 activity, which led to enhanced osteoclastogenesis and bone resorption ( Yuan L. et al, 2021 ). Hh pathway, an evolutionarily conserved signaling pathway, plays critical roles in skeletal development and homeostasis, and is regarded as a promising anabolic pathway for treating osteoporosis and promoting bone regeneration.…”
Section: The Differentiation Of Osteoclastsmentioning
confidence: 99%
“…MVP has also been implicated in suppression of metabolic diseases, such as obesity and atherosclerosis, through IKK-NF-ÎşB signaling-mediated inflammation ( 158 ). MVP negatively regulates osteoclast differentiation by inhibiting the calcineurin-NFATc1 signaling pathway ( 159 ). Moreover, it interacts with Src in an epidermal growth factor (EGFR)-dependent manner and downregulates Src tyrosine kinase activity in stomach tissue, with this latter being necessary for activation of extracellular signal-regulated kinase (ERK) signaling ( 160 ).…”
Section: Major Vault Protein (Mvp) Modulates Immune Signaling and Pathogen Entrymentioning
confidence: 99%